Supply Chain Management Strategies to Enhance Competitiveness and Foster Innovation through Cost Reduction in the Supply Chain - Ccala Quispe, Liz Mishel; Barreto Pila, Javier; Melgarejo Aliaga, David Martín (LACCEI, 2025)
A systematic literature review (SLR) was conducted to analyze strategies and technologies employed in supply chain management to enhance competitiveness and foster innovation in industrial companies. After screening 349 records, 40 relevant articles published between 2019 and 2024 were selected for analysis. The review identified key findings, including a constant increase in research on supply chain management, with Asia, particularly China, leading in publication volume. Common issues such as low competitiveness and productivity were found to impact operational efficiency, with advanced technologies, process standardization, strategic alliances, and continuous staff training highlighted as crucial interventions for improving competitiveness. The study concludes that managing and innovating within the supply chain is vital for enhancing the competitiveness and sustainability of industrial companies.